Sosialisasi Pencegahan Kanker Serviks pada Wanita Usia Subur dan Remaja - Liliek Pratiwi; Rusmiyati Rusmiyati (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
Cervical cancer is one of the most common types of cancer in women, especially in developing countries, including Indonesia. As the disease often goes undetected in its early stages, education and prevention are crucial. The purpose of this study is to increase public awareness on how to prevent cervical cancer in post-fertile women and Adolescents. The method used in this service is by means of socialization activities carried out through seminars, interactive discussions, and dissemination of educational materials. The materials contained information on the risk factors and symptoms of HPV and vaccination. A total 30 participants participated in this active, and the evaluation results showed that after the socialization, participants had a better understanding of cervical cancer. Result show that health education is essential to prevent cervical cancer. The conclusion was that participants’ knowledge of cervical cancer after socialization increased significantly. Activities like this are expected to increase public awareness about cervical cancer and encourage proactive measures to maintain reproductive health.